2016
DOI: 10.1007/s40839-016-0024-2
|View full text |Cite
|
Sign up to set email alerts
|

The multicultural and multi-religious Norwegian kindergarten

Abstract: This paper investigates the concept of ''the multicultural'' as it informs the national guidelines for Norwegian kindergarten teacher education (KTE). According to these guidelines, KTE students should gain multicultural knowledge that encompasses exposure to different religious beliefs. The results of an empirical study on multi-religious kindergartens in Norway serve as the context for this analysis, which identifies discrepancies between the multicultural ideal suggested in the guidelines and the realities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…294-97). In the article "The multicultural and multi-religious Norwegian kindergarten", Kari Krogstad shows that there is little coherence between the ideals of the state documents and the practical day to day activities in the kindergartens (Krogstad 2016(Krogstad , 2017. Audun Toft and Kristine Toft Rosland studied religious festivals in a sample of kindergartens and found that religious festivals other than those of Christians were not given attention (Toft and Rosland 2014).…”
Section: Relevant Research On Religion In Ececmentioning
confidence: 99%
See 1 more Smart Citation
“…294-97). In the article "The multicultural and multi-religious Norwegian kindergarten", Kari Krogstad shows that there is little coherence between the ideals of the state documents and the practical day to day activities in the kindergartens (Krogstad 2016(Krogstad , 2017. Audun Toft and Kristine Toft Rosland studied religious festivals in a sample of kindergartens and found that religious festivals other than those of Christians were not given attention (Toft and Rosland 2014).…”
Section: Relevant Research On Religion In Ececmentioning
confidence: 99%
“…Audun Toft and Kristine Toft Rosland studied religious festivals in a sample of kindergartens and found that religious festivals other than those of Christians were not given attention (Toft and Rosland 2014). Krogstad also studied culturally diverse kindergartens alone and together with Kari-Mette W. Hidle (Krogstad and Hidle 2015;Krogstad 2014Krogstad , 2016Krogstad , 2017; see also Iversen and Krogstad 2020). A common important finding in these studies is that dissemination of information about religions other than Christianity was neglected in the pedagogical practice in the public kindergartens studied.…”
Section: Relevant Research On Religion In Ececmentioning
confidence: 99%
“…A recent study (Perryman et al, 2020) using CCPT to measure the effectiveness of academic achievement did report demographic data that did include the ethnicity of the participants but did not investigate differential functioning of the groups. Furthermore, it is concerning since a little over half of the public K-12 population are from underrepresented racial–ethnic groups (Krogstad, 2019). Similarly, from 2000 to 2017, the United States experienced an increase in people from all racial–ethnic backgrounds; however, there was a significantly faster increase in people who identify as being Latinx (64%), Asian (74%), Pacific Islander (56%), and two races or more (200%) compared to all racial–ethnic groups (de Brey et al, 2019).…”
Section: Mental Health and Academic Achievementmentioning
confidence: 99%
“…Chapter 2 (appendix A) includes definitions of key terms such as "refugee". Krogstad, 2016. 246 Gonzalez-Barrera, 2015.…”
Section: Figure 18 Main Migration Countries In Northern America In 2015mentioning
confidence: 99%